A Bibliometric Analysis on Satisfaction and Loyalty in Homestay - Amin Kiswantoro; Sugiarto; Tonny Hendratono; Dwiyono Rudi Susanto; Damiasih; Nur Rohman; Rizky Maulana (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
This study aims to determine the mapping of research into several scopes of the tourism sector by discussing several topic parameters regarding satisfaction, loyalty, and homestay which were published during 2017 – 2022 and indexed on Google Scholar, analyzing topics related to Satisfaction and Loyalty in Homestay. This study uses a qualitative method with a thematic analysis approach as a data analysis method. This research utilizes the Publish or Perish (PoP) application to collect research data from research results indexed on Google Scholar by entering the keywords "Satisfaction and Loyalty in Homestay". Determination of the sample was carried out by screening publications in the form of journal articles, conference proceedings, book chapters, and books published from 2017-2022. The research data was analyzed using the VoS Viewer application. The results of mapping based on keywords illustrate that there is a research relationship related to the topic of Customer Loyalty with Effect, Guest Satisfaction, and homestay management, then the topic Effect is closely related to customer loyalty, satisfaction, development, perceived value, and tourism. Furthermore, research on the topic of tourism is closely related to community, development, effects, attractiveness, destination loyalty, homestay facilities, and other topics. From several existing research topics, future research can be carried out, such as the topic of risk management associated with the satisfaction and loyalty of tourists staying in homestays. This research was conducted only limited to data sources from Google Scholar so that future research can be developed with data sources originating from Scopus, Crossref, and IEEEXplore.